2019
DOI: 10.1111/ivb.12241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food, body size, and fragmentation on metabolic rate in a sessile marine invertebrate

Abstract: Metabolic rates vary among individuals according to food availability and phenotype, most notably body size. Disentangling size from other factors (e.g., age, reproductive status) can be difficult in some groups, but modular organisms may provide an opportunity for manipulating size experimentally. While modular organisms are increasingly used to understand metabolic scaling, the potential of feeding to alter metabolic scaling has not been explored in this group. Here, we perform a series of experiments to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…Food availability has been demonstrated to affect the pumping rate of sponges and other suspension filter feeders such as polychaetes, bivalves, ascidians, and bryozoans (Winter, 1973;Frost, 1980;Navarro and Winter, 1982;Robbins, 1983;Stuart and Klumpp, 1984;Riisgård and Ivarsson, 1990;Riisgård, 1991;Petersen and Riisgård, 1992;Petersen et al, 1999;Schuster et al, 2019). These studies observed a pattern characterized by a decrease in pumping rate with the increase in food concentration that was attributed to a regulation of food uptake, in such a way that the number of filtered particles remained constant as a protection against overloading of the feeding system (Winter, 1973;Navarro and Winter, 1982;Robbins, 1983;Riisgård and Ivarsson, 1990;Riisgård, 1991;Petersen and Riisgård, 1992;Petersen et al, 1999).…”
Section: Environmental Factors Affecting Pumping Ratementioning
confidence: 99%
“…Food availability has been demonstrated to affect the pumping rate of sponges and other suspension filter feeders such as polychaetes, bivalves, ascidians, and bryozoans (Winter, 1973;Frost, 1980;Navarro and Winter, 1982;Robbins, 1983;Stuart and Klumpp, 1984;Riisgård and Ivarsson, 1990;Riisgård, 1991;Petersen and Riisgård, 1992;Petersen et al, 1999;Schuster et al, 2019). These studies observed a pattern characterized by a decrease in pumping rate with the increase in food concentration that was attributed to a regulation of food uptake, in such a way that the number of filtered particles remained constant as a protection against overloading of the feeding system (Winter, 1973;Navarro and Winter, 1982;Robbins, 1983;Riisgård and Ivarsson, 1990;Riisgård, 1991;Petersen and Riisgård, 1992;Petersen et al, 1999).…”
Section: Environmental Factors Affecting Pumping Ratementioning
confidence: 99%
“…We collected ~80 sexually mature B. neritina colonies from the Royal Melbourne Yacht Squadron in Port Phillip Bay, Victoria, Australia (37°51''43.1''S, 144°57'51.2''E) in March and April 2018. To obtain individuals for our experiments, we spawned colonies according to standard procedures (Schuster et al 2019). Briefly, we kept colonies in the laboratory in field-collected seawater in aerated tanks in the dark.…”
Section: Study Species Site and Field Deploymentmentioning
confidence: 99%
“…Phenotypic plasticity of standard and basal metabolic rate in response to changing food availability is found across a wide variety of taxa including invertebrates [20,46] and all major vertebrate classes such as fish [12,21,47,48], amphibians [49], reptiles [22,50], birds [51][52][53][54] and mammals [55,56]. Changes in energy metabolism occur over timescales ranging from days to weeks [47,57] and differ considerably among individuals [12,21,48,57].…”
Section: Metabolic Responses To Short-term Changes In Food Availabilitymentioning
confidence: 99%